Workshop Penguatan Karakter Anti Bullying dan Wirausaha Siswa Melalui Program Student Preneurship di UPT SDN 73 Bontorita 1 - Sirajuddin, Sirajuddin; Gita, Gita; Wahyuningsih, Sri; Rifki Fauzan, Andi; Dzakiyah Nuradillah, Nahda; Fijriani, Nur; Mulya Ramadani, Suci; Mutiara, Mutiara; Nurafni, Nurafni (Jurnal Pengabdian Kepada Masyarakat Patikala, 2026)
The workshop titled "Strengthening Anti-Bullying Character and Student Entrepreneurship through the Student Preneurship Program" was conducted as an effort to instill positive character values while fostering an entrepreneurial spirit among elementary school students. This activity was motivated by the increasing prevalence of bullying in elementary schools both verbal, social, and physical and students’ lack of awareness regarding empathy and social responsibility. The workshop was held on Thursday, September 25, 2025, at UPT SDN 73 Bontorita I, Galesong District, Takalar Regency, involving academic speakers, teachers, parents, and KKN-DIK 2025 students. The implementation method consisted of three main stages: planning, implementation, and evaluation. During the implementation stage, students were divided into four groups to create simple products containing anti-bullying campaign messages. The results indicated that students developed a deeper understanding of bullying and its effects while expressing positive messages through creative entrepreneurship. Furthermore, the involvement of teachers and parents strengthened the internalization of character values and enhanced peer communication. Therefore, this program serves as an effective educational innovation for promoting anti-bullying behavior and nurturing entrepreneurial skills among elementary school students.